“The Penance of Life”: The Testimonial Paradigm in Coleridge’s The Rime of the Ancient Mariner - Wright, Jude (Romanticism on the Net)

(untitled) (Université de Montréal, 2018)
This article argues that The Rime of the Ancient Mariner’s curious and much commented on theology is best accounted for by examining it in relation to a shift in religious discourses. The poem evidences a disconcerting shift from a Catholic confessional dynamic to one closer akin to an Evangelical paradigm of testimony. As such, the article begins by accounting for the importance of testimony (and its theological logic) in the Evangelical milieu which spread across Britain during Coleridge’s early to middle years. It next examines Coleridge’s developing religious thought in relation to Evangelical concepts, pointing to the significance of what J. Robert Bart termed a “balance” between “man’s work and God’s work in the process of faith; man’s will and God’s will; rational argumentation and divinely granted revelation; objective evidence and subjective religious experience.” Upon situating Coleridge in relation to Evangelical concepts of witnessing, the article more fully examines The Rime of the Ancient Mariner, focusing on the shift in theological logic that changes a kind of Catholic confessional impulse towards an on-going urge to testimony, finally linking the burning feeling that compels the Mariner’s testimony to the Pentecost event as related in the New Testament book of Acts.